PERANAN CAMAT DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR KECAMATAN SANGATTA UTARA KABUPATEN KUTI TIMUR - Artanti Artanti (ADMINISTRASI PUBLIK, 2019)
This research is motivated by a problem where the influence of the role of the Camat is not optimal in improving employee performance. then a leader must be truly - qualified to be able to lead his subordinates well so that productivity and organizational goals can be achieved effectively and efficiently. Camat has functional authority to supervise employees under their leadership. The role of the Camat in improving employee performance at the Sangatta North District Office, it is desirable that the employees be directed and professional, so that it is easier to achieve a goal to be achieved with employees in the Sangatta North District office. Lack of employee discipline because there are still employees who are not on time to enter the office, employees tend to ignore work when the Camat is not in place. In this case, the Head of District must be able to encourage the performance of employees by encouraging, directing and motivating employees to work together in realizing the vision, mission and values of the organization.This study aims to determine the role of North Sangata Sub-District Chief in improving employee performance by using theory according to Henry Mintzberg (2000) that the roles usually run by leaders in improving a performance, namely; role a. Interpersonal Role such as Figure head, Leader, Liasion. b. Decison Making (Role of decision makers) such as Entreprenuer, Distrubance handler, Resource allocation, Negotiator. c. Informational role (Role of information sources) such as Monitor and Dessiminator, Spoke person. This study uses a descriptive qualitative approach. Data collection techniques are carried out by observation, interview, and document study techniques.The results of the study show that the role of the Sangatta North Sub-district in improving employee performance at the Sangatta North Sub-District Office always carries out its role as an interpersonal role, decision making and informational role in improving employee performance at the Sangatta North District Office